The Development and Validation of STEM Major Embeddedness and University Embeddedness Scales. Issue 5 (19th October 2020) - Major, Debra A.; Cigularov, Konstantin P.; Litano, Michael L.; Streets, Valerie N.; Henson, James M.; Reynoldson, Katelyn R.
ABSTRACT: Ensuring the adequacy of the science, technology, engineering, and mathematics (STEM) workforce is a priority in the United States. STEM persistence in college is essential to building career pathways, but research is needed to explain voluntary attrition. We applied embeddedness theory to develop and evaluate a 14-item measure of STEM major embeddedness and a 12-item measure of university embeddedness. Using multiple undergraduate samples, we conducted item-sort tasks, exploratory factor analyses, and confirmatory factor analyses to ensure psychometric quality and to refine multidimensional scales, each with dimensions of fit, links, and sacrifice. Findings supported content, convergent, discriminant, and criterion-related validity. Mapping the nomological network, embeddedness was related to social and human capital, major satisfaction, major commitment, and persistence. Future research and practical applications are discussed.